Differences in Service Position Against Service Accuracy in Volleyball - Hiskya, Hendra Jondry; Dwi Kuswoyo, Dilli; Umakaapa, Muktamar (Indonesian Journal of Physical Education and Sport Science, 2023)
Purpose study. This study aims to find out the difference between serving for volleyball from behind position one, serving from behind position six, and serving from behind position five for UKM Volleyball UNMUS players, also to find out which is more effective between serving from behind position one. serving from behind position six, and serving from position five on top serving ability. Materials and methods. The subjects of this study were 21 UNMUS volleyball players. Data collection uses tests, with instruments in the form of service accuracy tests carried out from the right, left and center positions. The t-value for service accuracy between the right position and the left position is 0.225 and the calculated significant value (Sig) is 0.824. The t value for service accuracy between the right position and the middle position is 0.846 and the calculated significant value (Sig) is 0.407. The t value for service accuracy between the left position and the middle position is 1.091 and the calculated significant value (Sig) is 0.288. The data analysis technique uses ANOVA analysis and t-test through the prerequisite test for normality and homogeneity. Results. The results showed that there was no significant difference in the accuracy of the top serve from different positions, namely from the right, left and center positions. In detail, there is no significant difference in the accuracy of services performed from the right and left positions, the accuracy of services performed from the right and center positions, the accuracy of services performed from the left and center positions. Conclusions. Research results conclude that No There is significant difference accuracy service performed from position left and position in the middle of UKM Musamus Merauke University Volleyball players.